(untitled) (Research, Society and Development, 2020)
The recent environmental impacts have been causing a growing concern with anthropic actions and their consequences in nature, as well as with the future of the planet. This fact is evidenced through the countless International Conferences and Agreements carried out in the last decades by great nations and organizations, with the objective of defining goals or creating legislation that may mitigate or slow down the effects of these impacts. The Environmental Education comes from this concern and it is extremely important that its approach, like that of other environmental concepts, be introduced in the initial series of teaching, a stage where the individual is in the process of building conception and worldviews. The objective of the present paper is to emphasize, through a literature review, the importance of EE in Brazilian basic education, based on the conceptions of Henri Wallon, Lev Vygotsky and Jean Piaget, famous thinkers of the 20th century and that are still today references for the study of human psychology. The study was carried out by consulting articles, monographs, dissertations and other documents in virtual Scielo databases and institutional repositories. It is expected that, with the introduction of these concepts even at this stage of structuring personality and citizenship, it will be possible to form future critical adults who are aware of the impact of their actions on the environment.